Stranger in the woods : a photographic fantasy - Sams, Carl R.; Stoick, Jean. (Milford, MI : Carl Sams II Photography, 2000)
The resident birds and animals react to a snowman appearing in their woods after a winter storm.
5.3
3-6.
3-6
Keywords: Animals -- Fiction; Birds -- Fiction; Forests and forestry -- Fiction; Snowmen -- Fiction; Winter -- Fiction; Animals -- Fiction; Birds -- Fiction; Forests and forestry -- Fiction; Snowmen -- Fiction; Winter -- Fiction